The Mutual Interaction effects between Array Antenna Parameters and Receiving Signals Bandwidth - Mohammed, Bassim S.; Ahmed, Emad S.; Sateaa, Shahad D. (Al-Khwarizmi Engineering Journal, 2017)
The presence of a single complex adaptive weight in each element channel of an adaptive array antenna is sufficient for processing of narrowband signals. The ability of an adaptive array antenna to null interference deteriorates rapidly as the interference bandwidth increases. The performance of narrowband adaptive array antenna with LMCV Beamforming algorithm is examined. The interaction effects between received signal angle of arrival and array parameters like the interelement spacing and the number of array element and the received signal bandwidth were studied. The output Signal to Interference plus Noise Ratio (SINR) and Interference to Noise Ratio (INR) are used as performance parameters for evaluation of these effects. It is found that the amount of degradation in the output SINR is increased significantly with the increase of array interelement spacing, number of array elements and when the angle of arrival of received signals are closet to end fire.